FROM THE HISTORY OF THE EMERGENCE OF ANCIENT INDIAN STATEHOOD (TAMADDUN NURI JURNALI, 2025)
A number of studies are being conducted in the world on the ancient traditions of statehood and urban planning in India, migration processes in the region, and their influence on the lives of the peoples of the region. This article discusses these matters.